2019
DOI: 10.1109/access.2019.2904201
|View full text |Cite
|
Sign up to set email alerts
|

Empirical Based Ranging Error Mitigation in IR-UWB: A Fuzzy Approach

Abstract: Indoor tracking and navigation (ITN) mainly depend on indoor localization. An impulse radio ultra-wideband (IR-UWB) is the most advanced technology for precision indoor localization. Besides its precision, the IR-UWB also has low complex hardware, low power consumption, and a flexible data rate that makes it the ideal candidate for ITN. However, two significant challenges impede the achievement of highresolution accuracy and optimum performance: non-line-of-sight (NLOS) channel condition and multipath propagat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(10 citation statements)
references
References 27 publications
(53 reference statements)
0
10
0
Order By: Relevance
“…The effects of MPCs can be modeled as a bias error parameter in the model of the localization problem, and can be solved by using several tools such as convex optimization and sparse estimation methods [150]. It was demonstrated that fuzzy logic can be a useful tool for inferring the MPCs error with considerably less computational demand [149]. Furthermore, when the sensor nodes change their positions in time, several techniques based on the extended Kalman filter and particle filter can be used to track the positions of the TN and bias error caused by the MPCs [148,151,171].…”
Section: ) Mitigation Of Multipath Componentsmentioning
confidence: 99%
“…The effects of MPCs can be modeled as a bias error parameter in the model of the localization problem, and can be solved by using several tools such as convex optimization and sparse estimation methods [150]. It was demonstrated that fuzzy logic can be a useful tool for inferring the MPCs error with considerably less computational demand [149]. Furthermore, when the sensor nodes change their positions in time, several techniques based on the extended Kalman filter and particle filter can be used to track the positions of the TN and bias error caused by the MPCs [148,151,171].…”
Section: ) Mitigation Of Multipath Componentsmentioning
confidence: 99%
“…Model level [147][148][149][150][151][152] The effects of the MPCs are modeled as additive biases. The sparsity of the MPCS on the localization model can be exploited.…”
Section: Mitigationmentioning
confidence: 99%
“…However, the overfitting & underfitting, parameter tuning and processing time of data from CNN models give challenges to the UWB localization. Most recent works on deep learning for UWB localization are explained in References [23][24][25]. The discussed localization systems from References [23][24][25] effectively minimize the ranging errors and computational burden and achieve excellent localization performance with much lower network complexity for UWB indoor localization.…”
Section: Related Workmentioning
confidence: 99%